Instalación de una nueva troncal para el mejoramiento del sistema de distribución de relleno hidráulico del tajo 370, mina San Ignacio De Morococha - 2018 - Davila Tantalean, Luis Eduardo (2019)
Stuffing science began to flourish in the 1950s, with simple tests of sands and coal pumping in moderate concentrations. This science has gradually evolved to include pulp pumping in the food industry and process industries, coal and oil blends as new fuels and numerous mixtures of minerals with water. What is transported is a pulp that is a mixture of solids and liquids in different proportions whose physical characteristics depend on factors such as the type of ducts for transport, viscosity, pulp density among others. This work is carried out in the San Ignacio mine of Morococha, whose geology allows to exploit these mineralized bodies under the mechanized cutting and filling method and chambers and pillars, to achieve the established production objectives, using appropriate machinery for these purposes from dumpers and dumpers. and brought to surface with trolley line directly from the Ore pass, to guarantee this the service system must be optimal, one of them filling the exploded pits to be able to return the stability to the structures, to give floor for work for the machinery in conditions safe thus speeding the mining cycle. This is the origin of the main objective in this research work; it implies to make a study about the feasibility of using an old carbon steel pipe, for the transport of hydraulic fill to the exploitation pits as is the case of study the TJ370. The study arises from the change of pipes (polyethylene pipes), which at a lower level were not complying with the required flow due to structural failures (breakage) that prevented the fulfillment of the objectives proposed in the mine. Faced with this problem we proceeded to use an old carbon steel pipe which is extended by already exploited works and through a Raise Boring chimney, which was used for ventilation, the pipe was communicated with the pit through polyethylene pipe. By making the respective changes, the pipe pressure is relieved by the difference in heights, thus avoiding problems in the pipes. In addition, as the carbon steel pipe has greater strength and is uniform, it allows to increase the percentage of solids that can be sent through the pipeline (a higher density) of 1600gr/l to 1850gr/l measured with the Maroy scale, under this parameter the average time that a pit is filled decreases significantly, increasing the pressure of the pump and with basic safety considerations, the change was made, achieving to be above the established production levels by an additional 20%.